2021
DOI: 10.1007/s00213-021-06028-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the SLC6A3 3’ UTR VNTR in nicotine effects on cognitive, affective, and motor function

Abstract: Rationale Nicotine has been widely studied for its pro-dopaminergic effects. However, at the behavioural level, past investigations have yielded heterogeneous results concerning effects on cognitive, affective, and motor outcomes, possibly linked to individual differences at the level of genetics. A candidate polymorphism is the 40-base-pair variable number of tandem repeats polymorphism (rs28363170) in the SLC6A3 gene coding for the dopamine transporter (DAT). The polymorphism has been associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 96 publications
(148 reference statements)
0
1
1
Order By: Relevance
“…Contrary to our hypotheses, we did not observe interactions of background and target velocity for any of the dependent variables although we had purposely selected stimuli conditions that had yielded a strong interactive effect in a prior behavioural study (Schröder et al, 2021). A reason for this discrepancy could be that pursuit performance was generally worse compared to previous laboratory investigations using similar tasks (Meyhöfer et al, 2019;Schröder et al, 2021;Schröder et al, 2022) presumably because of the unusual and uncomfortable environment in the scanner and distracting external stimuli such as scanner noise in this study (see also Koch et al, 2003). Therefore, it can be assumed that participants did not reach optimal performance levels and thus more subtle effects such as the interaction reported previously could not emerge.…”
Section: Behavioural Effectscontrasting
confidence: 80%
“…Contrary to our hypotheses, we did not observe interactions of background and target velocity for any of the dependent variables although we had purposely selected stimuli conditions that had yielded a strong interactive effect in a prior behavioural study (Schröder et al, 2021). A reason for this discrepancy could be that pursuit performance was generally worse compared to previous laboratory investigations using similar tasks (Meyhöfer et al, 2019;Schröder et al, 2021;Schröder et al, 2022) presumably because of the unusual and uncomfortable environment in the scanner and distracting external stimuli such as scanner noise in this study (see also Koch et al, 2003). Therefore, it can be assumed that participants did not reach optimal performance levels and thus more subtle effects such as the interaction reported previously could not emerge.…”
Section: Behavioural Effectscontrasting
confidence: 80%
“…In a study examining the effects of smoking on mood, it was stated that smoking had a calming effect on anger in women and on anger and sadness in men (23) and that nicotine replacement has been shown to be effective in controlling agitation in smokers with schizophrenia (9). In the literature, it has been defined that smoking and environmental factor such as stress are associated, and the assumption that patients with schizophrenia tend to selfmedicate by smoking due to symptoms of mental illness, drug side effects and cognitive deficits has been mentioned (24). Also, the relationship between recurrent disease course and stressful life events in schizophrenia has been investigated, and it has been reported that patients with schizophrenia tend to experience stress more intensely and that this is caused by less effective approaches to coping with stress (25).…”
Section: Discussionmentioning
confidence: 99%